Feedback as a methodological strategy to improve speaking skill - Luzón Rodrigues, Jessica Carolina (2024)
The main objective of this study is to analyze the relationship between feedback and the development of oral expression skills in English in ninth grade students at Juan de Velasco High School. A qualitative methodological approach was used to obtain a detailed understanding of the pedagogical strategies used by the teacher and students to promote communicative skills in English. The research design was both exploratory and field-based, which allowed us to investigate the experiences, perceptions and practices of teachers and students in their natural context. The study population consisted of ninth grade students, parallel “H”, and their English teacher. For data collection, two main instruments were used: a classroom observation guide and a semi-structured interview. The instruments allowed us to directly investigate the interactions between students and teacher, as well as the feedback strategies used. The results indicated significant inconsistencies in the application of feedback in the classroom. Although basic feedback strategies were identified, such as direct verbal correction, the absence of more structured practices, such as recast feedback, peer correction, and other strategies showed significant inconsistencies in the application of feedback in the classroom. In the process of triangulation of the obtained data, it was possible to demonstrate the limited knowledge of feedback strategies used in the classroom and the need to implement more systematic and varied feedback to optimize oral learning of the foreign language.